Correction: Reduced activity, reactivity and functionality of the sympathetic nervous system in fibromyalgia: An electrodermal study - Reyes del Paso, Gustavo A.; de la Coba, Pablo (PloS one, 2020)
[This corrects the article DOI: 10.1371/journal.pone.0241154.].